Analysis of employees’ social and psychological component indicators in the structure of higher education institution image - Boltivets, Sergii (2020)
The article presents the analysis of social and psychological component indicators of academic employees in the structure of higher education institution (university) image. As a part of comprehensive study we determined the internal structure of a higher education institution image according the results of factor and correlation analysis which includes five factors: professional, social-psychological, motivational, emotional-volitional and individual-psychological. This approach gave a possibility to characterize the peculiarities of each factor, published in scientific articles, influence on the image of the university. Some of the factors have been stydied previously and we could find scientific publications on these issues. At the same time the results of the social and psychological component research have not been published yet but have a significant scientific interest since they characterize a sample of 285 representatives of the rectorate, dean's offices, heads of departments and academic staff of the university. We found out that each category of respondents has its own peculiarities regarding the level of satisfaction with quality of life, subjective satisfaction or not satisfaction with social or personal recognition, material and social security, level of personal authority. We were able to find the dominant type of university employees’ attitude towards people in interaction: authoritarianism, egoism, aggression, suspicion, subordination, dependence, friendliness and altruism. The results of this study can be used for individual diagnosis and appropriate correction of each category of the respondents to have a positive impact on the image of the university.